SEISMIC ISOLATED HOUSE REACTION UPON CONDITION OF THE REPEATABILITY OF EARTHQUAKES - Lapin, Vladimir; Sharipov, Rashid; Aldakhov, Yerkin (Journal of Applied Engineering Science, 2022)
To study the seismic properties of buildings in Almaty, a special test site operates. It includes buildings with conventional strip foundations with a system of cross belts and seismic support of 2 types. The landfill buildings were previously tested under static and dynamic influences. With the use of real accelerograms of earthquakes, a forecast of the behavior of a seismically isolated house on kinematic foundations under seismic influences has been carried out. The seismic impact is represented by a set of real accelerograms of strong, mainly Californian earthquakes. The hearts depths and magnitudes correspond to possible Almaty earthquakes. Two design schemes of a seismically isolated building are considered - single-mass and 10-mass dynamic building models. It is shown that the magnitudes of displacements in the kinematic foundations (KF) level obtained by two dynamic models usually differ within 5-10%. Therefore, the calculation of seismically isolated buildings can be applied to a single-mass non-linear dynamic model. A linear regression connection was obtained between the values of acceleration at the base and displacements at the level of the foundation. For the values of acceleration according to the new "Map of seismic zoning of the Republic of Kazakhstan" were obtained the predicted values of displacement at the level of the kinematic support of the order of 8.0-11.5 cm.
Keywords: seismic isolation, accelerogram, safety, forecast, foundation, computational model, earthquake recurrence